Oleuropein aglycone and polyphenols from olive mill waste water ameliorate cognitive deficits and neuropathology. (21st May 2016) - Pantano, Daniela; Luccarini, Ilaria; Nardiello, Pamela; Servili, Maurizio; Stefani, Massimo; Casamenti, Fiorella
Abstract : Aim: In TgCRND8 (Tg) mice we checked the dose–response effect of diet supplementation with oleuropein aglycone (OLE) at 12.5 or 0.5 mg kg −1 of diet. We also studied the effects of dietary intake of the mix of polyphenols present in olive mill waste water administered at a total dose as high as the highest dose of OLE (50 mg kg −1 of diet) previously investigated. Methods: Four month‐old Tg mice were equally divided into four groups and treated for 8 weeks with a modified low fat (5.0%) AIN‐76 A diet (10 g day −1 per mouse) as such, supplemented with OLE (12.5 or 0.5 mg kg −1 of diet) or with a mix of polyphenols (50 mg kg −1 of diet) found in olive mill waste water. Behavioural performance was evaluated by the step down inhibitory avoidance and object recognition tests. Neuropathology was analyzed by immunohistochemistry. Results: OLE supplementation at 12.5 mg kg −1 of diet and the mix of polyphenols was found to improve significantly cognitive functions of Tg mice ( P < 0.0001). Aß42 and pE‐3Aß plaque area and number were significantly reduced in the cortex by OLE and in the cortex and hippocampus by the mix of polyphenols ( P < 0.01, P < 0.001 and P < 0.0001). Similar autophagy induction was found in the brain cortex of differently treated mice. Conclusion: Our results extend previous data showing that the effects of OLE on behavioural performance and neuropathology are dose‐dependent and not closely related to OLE by itself. In fact, diet supplementation with the same dose of a mix of polyphenols found in olive mill waste water resulted in comparable neuroprotection.